FUNGSI PERENCANAAN DAN PENGGERAK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI INPRES HEDAM ABEPURA KOTA JAYAPURA - AGNES ARYESAM (Jurnal Ilmu Pendidikan Indonesia, 2018)
This qualitative descriptive research has two types of data resources, namely primary data and secondary data. The primary data were the result of the interview from the data resources which determined through the purposive sampling technique.  The primary data were obtained from the headmaster, teachers, administrative staff, school committees, and students. While the secondary data includes textbooks,   school documents, journals, theses, dissertations, internet sites, which related to the implementation of the principal's management functions in improving the quality of education. Data were collected through in-depth interview techniques with informants, observation, and documentation. In analyzing the data, the researcher applied the qualitative descriptive techniques based on Miles and Huberman theory namely data reduction, data exposure, and data verification. There are two objectives of the research, they are 1) to describe the implementation of planning function and 2) to describe the implementation of the actuating function of the principal in improving the quality of education at Hedam Inpres State Elementary School in Abepura, Jayapura. The study revealed that 1) the principal of Hedam Inpres State Elementary School in Abepura, Jayapura has implemented the planning function properly and 2) The actuating function of the school principal had not been implemented yet. Keywords: Principal Management Functions, Planning, Actuating, Quality of Education